Does the Swiss Debt Brake Induce Sound Federal Finances? A Synthetic Control Analysis - Christian F. Pfeil; Lars P. Feld (Center for Economic Studies and ifo Institute (CESifo), 2016)
The Swiss debt brake is widely appreciated as one of the most rationally designed fiscal rules in the world and was thus also discussed as blueprint in the debates about fiscal rules in Germany, the European Union member states and Israel. However, evidence that this rule really contributes to sound federal finances does not exist yet. We investigate the effectiveness of the Swiss debt brake by employing the Synthetic Control Method. We find that the introduction of this fiscal rule improved the budget balance by about 3.6 percentage points on average in a post-intervention period covering five years.
Keywords: H11; H60; 330; Swiss debt brake; cyclically adjusted budget balance; government debt; synthetic control method